2011
DOI: 10.4312/dp.38.24
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of settlement strategies to environmental conditions in southern Slovakia in the Neolithic and Eneolithic

Abstract: Environmental conditions such as climate, topography, and soil conditions had an impact on prehistoric settlement strategies. By studying changes in settlement structure in the Nitra, Hron and Ipel’ valleys in southern Slovakia over the course of the Neolithic and Eneolithic, preferences for various climatic and topographic environments in different periods can be seen. Besides cultural and socio-economic factors, it can also be expected that changes in climate contributed to change in settlement patterns. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…4000 to 3500 BC, followed by drought conditions ca. 3500 to 3000 BC, finally shifting back to humid condition for the end of the Copper Age (Tóth et al 2011). In Hungary, interpreting climatic fluctuations can be difficult with two major climatic boundaries roughly corresponding with the Great Hungarian Plain (to the east), which is arid and continental, and Transdanubia (to the west), which is more humid and moderate (Nagy-Bodor et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…4000 to 3500 BC, followed by drought conditions ca. 3500 to 3000 BC, finally shifting back to humid condition for the end of the Copper Age (Tóth et al 2011). In Hungary, interpreting climatic fluctuations can be difficult with two major climatic boundaries roughly corresponding with the Great Hungarian Plain (to the east), which is arid and continental, and Transdanubia (to the west), which is more humid and moderate (Nagy-Bodor et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Archaeological investigations in the surrounding region support the scenario that the erosion was initiated by human activities (Tóth et al . ). It is also proved by the finding of a ceramic shard dated to 7350 cal.…”
Section: Discussionmentioning
confidence: 97%
“…Early arrival of the Neolithic people to the Danubian Lowland allow their further survival at the artificialy open habitats created by man (Tóth et al . ). Latter spreading of human settlements to higher elevations likely reached the majority of the spring fens already overgrown by forest during the middle Holocene (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The climate of the basin is relatively warm and continental, with rather low precipitation sums with maxima during the summer. There is a rich history of human activities and extensive agricultural use since the Neolithic (Tóth et al, 2011). Study area with study sites and their classification to biogeographical regions shown.…”
Section: Study Areamentioning
confidence: 99%